Temporal variability of tropospheric ozone and ozone profiles in the Korean Peninsula during the East Asian summer monsoon: insights from multiple measurements and reanalysis datasets - J. Bak; E.-J. Song; E.-J. Song; H.-J. Lee; H.-J. Lee; X. Liu; J.-H. Koo; J. Kim; W. Jeon; W. Jeon; J.-H. Kim; C.-H. Kim; et al. (Atmospheric Chemistry and Physics, 2022)
We investigate the temporal variations of ground-level ozone and balloon-based ozone profiles at Pohang (36.02∘ N, 129.23∘ E) in the Korean Peninsula. Satellite measurements and chemical reanalysis products are also intercompared to address their capability of providing consistent information on the temporal and vertical variability of atmospheric ozone. Sub-seasonal variations of the summertime lower-tropospheric ozone exhibit a bimodal pattern related to atmospheric weather patterns modulated by the East Asian monsoon circulation. The peak ozone abundances occur during the pre-summer monsoon with enhanced ozone formation due to favorable meteorological conditions (dry and sunny). Ozone concentrations reach their minimum during the summer monsoon and then re-emerge in autumn before the winter monsoon arrives. Profile measurements indicate that ground-level ozone is vertically mixed up to 400 hPa in summer, while the impact of the summer monsoon on ozone dilution is found up to 600 hPa. Compared to satellite measurements, reanalysis products largely overestimate ozone abundances in both the troposphere and stratosphere and give inconsistent features of temporal variations. Nadir-viewing measurements from the Ozone Monitoring Instrument (OMI) slightly underestimate the boundary layer ozone but represent the bimodal peaks of ozone in the lower troposphere and the interannual changes in the lower-tropospheric ozone in August well, with higher ozone concentrations during strong El Niño events and low ozone concentrations during the 2020 La Niña event.